2019
DOI: 10.2478/sues-2019-0012
|View full text |Cite
|
Sign up to set email alerts
|

The Consequences of Shadow Economy and Corruption on Tax Revenue Performance in Nigeria

Abstract: Shadow economy and corruption are the two harmful activities that do not work in the favour of tax revenue performance. As a result it renders an effective government incapacitated and unable to carry out its social responsibilities. This study considers the effect of the informal economy and graft on tax revenue performance in Nigeria using secondary data that cover a period from 1996 to 2018. This period has been covered by the corruption perception index captured by the Transparency International for Nigeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…However, various studies show that the shadow economy has a negative effect on tax revenue. This finding, among others, is based on research conducted by Bird et al (2004) based on data sets from 1990 to 1999 in a number of developing countries, Omodero (2019) based on the 1991 to 2018 dataset in Nigeria, and Khujamkulov (2017) based on 1980 to 2010 dataset in Tajikistan. Meanwhile, according to Indupurnahayu & Walujadi (2019) on average from 1990 to 2018, Indonesia lost potential tax revenue of 0.7% of gross domestic product due to the shadow economy.…”
Section: Effect Of Shadow Economy On Tax Revenuementioning
confidence: 71%
See 3 more Smart Citations
“…However, various studies show that the shadow economy has a negative effect on tax revenue. This finding, among others, is based on research conducted by Bird et al (2004) based on data sets from 1990 to 1999 in a number of developing countries, Omodero (2019) based on the 1991 to 2018 dataset in Nigeria, and Khujamkulov (2017) based on 1980 to 2010 dataset in Tajikistan. Meanwhile, according to Indupurnahayu & Walujadi (2019) on average from 1990 to 2018, Indonesia lost potential tax revenue of 0.7% of gross domestic product due to the shadow economy.…”
Section: Effect Of Shadow Economy On Tax Revenuementioning
confidence: 71%
“…Based on the coefficient value, it can be interpreted that a 1% increase in the proportion of shadow economy in the economies of South Asian and Asia-Pacific countries reduces tax revenue by 0.0968818% of the country's gross domestic product, ceteris paribus. Omodero (2019) in his research revealed that the shadow economy affects tax revenue because economic activities are not reported and not taxed. In line with this Khujamkulov (2017) emphasized that shadow economy activities are caused by several factors such as entrepreneurs and businesses that face burdensome tax regulations with weak law enforcement, so that state revenue from business is lost.…”
Section: Partial Analysis Of Independent and Moderating Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on arguments from the theoretical basis, previous studies, and an explanation of the study locus, we assessed the relationship between FDI, SS, CP, CC, IPT, SE, and TR by taking the following form: 2020), and Omodero (2019) who have investigated the relationship between these variables, so that it is very suitable to be applied in developing countries such as Indonesia.…”
Section: Modelmentioning
confidence: 99%